2011
DOI: 10.2967/jnmt.110.080358
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose to Technologists per Nuclear Medicine Examination and Estimation of Annual Dose

Abstract: Conventional diagnostic nuclear medicine applications have been continuously increasing in most nuclear medicine departments in Turkey, but to our knowledge no one has studied the doses to technologists who perform nuclear medicine procedures. Most nuclear medicine laboratories do not have separate control rooms for technologists, who are quite close to the patient during data acquisition. Technologists must therefore stay behind lead shields while performing their task if they are to reduce the radiation dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…The findings are in line with previous studies (Mettler et al 2009, Konishi et al 1994, Bayram et al 2011and Piwowarska-Bilska et al 2011 The radiation is most significant in the time immediately after injection. Our results reaffirm the conclusion from Konishi et al 1994 that "undue anxiety among hospital staff with regard to exposure to radioactive patients [and excreted urine from patients] must be placed in the proper perspective through education and training".…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings are in line with previous studies (Mettler et al 2009, Konishi et al 1994, Bayram et al 2011and Piwowarska-Bilska et al 2011 The radiation is most significant in the time immediately after injection. Our results reaffirm the conclusion from Konishi et al 1994 that "undue anxiety among hospital staff with regard to exposure to radioactive patients [and excreted urine from patients] must be placed in the proper perspective through education and training".…”
Section: Discussionsupporting
confidence: 93%
“…We used Bayram et als survey (Bayram et al 2011) as a methodological guide for measuring the radiation dose from patients. All measurements was obtained with a hand held dosimeter: RadEye B20 from Thermo Scientific.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation dose or dose rates per application and in total to staff within a time period such as daily, monthly or annually can be determined by two different methods (3,4,5,6,7,8). At first, it is calculated by measurements obtained at a fixed distance from the patient and some authors also take into consideration the time spent with the patient at a constant distance to calculate the amount of expected radiation exposure to technicians (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…A different study was conducted by Fog et al [11] using Monte Carlo techniques to simulate the effectiveness of a lead apron against 99m Tc and 18 F. This study found reasonable dose reductions when shielding against 99m Tc but minimal protection against the higher energies of 18 F. The study also reported varying degrees of dose escalation at small distances from behind a lead apron, although it was concluded that this would most likely be absorbed by the wearer's clothing. Other types of shielding that can be used include mobile shields, and their effectiveness was investigated by Bayram et al [12].…”
Section: Introductionmentioning
confidence: 99%